Sizing of Hybrid Energy Storage Systems for Inertial and Primary Frequency Control - Alves, Erick Fernando; Mota, Daniel dos Santos; Tedeschi, Elisabetta (Frontiers in Energy Research, 2021)
The exponential rise of renewable energy sources and microgrids brings about the challenge of guaranteeing frequency stability in low-inertia grids through the use of energy storage systems. This paper reviews the frequency response of ac power systems, highlighting its different time scales and control actions. Moreover, it pinpoints main distinctions among high-inertia interconnected systems relying on synchronous machines and low-inertia systems such as those with high penetration of converter-interfaced generation. Grounded on these concepts and with a set of assumptions, it derives algebraic equations to rate an energy storage system providing inertial and primary control. The equations rely on parameters typically defined by system operators, industry standards or network codes, are independent from the energy storage technology and robust to system nonlinearities. Using these results, the authors provide a step-by-step procedure to size the main components of a converter-interfaced hybrid energy storage system. Finally, a case study of a wind-powered oil and gas platform in the North Sea demonstrates with numerical examples how the proposed methodology: 1) can be applied in a practical problem; 2) allows the system designer to take advantage of different technologies and set specific requirements for each storage device and converter according to the type of frequency control provided.